2009
DOI: 10.1016/j.eplepsyres.2009.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Different phases of afterdischarge during rapid kindling procedure in mice

Abstract: SummaryThe basic mechanisms of hippocampal networks in epileptogenesis are not entirely understood. To help achieve a better understanding of these mechanisms, we studied the extra-cellular electricallyevoked responses in the hippocampi of mice during rapid kindling. Kindling protocol was achieved by stimulating the dorsal right hippocampus six times daily for four days using bipolar electrodes to produce sub-convulsive electrical discharges. Motor responses and analyzed electroencephalographic recordings show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…As shown in previous studies, animals that reach stage 3–5 (Racine’s scale score) and obtain an AD duration of more than 25 s maintain a similar score and duration at least 1 week after subconvulsive hippocampal stimulation (Tu & Bazan, 2003; Musto et al., 2009). Therefore, in our studies, groups treated with the PAF antagonist, LAU‐0901 (2,4,6‐trimethyl‐1,4‐dihydro‐pyridine‐3,5‐dicarboxylic acid ester), or vehicle (2‐hydroxypropyl‐β‐cyclodextrin,1.4 mg/kg, i.p.…”
Section: Methodssupporting
confidence: 57%
“…As shown in previous studies, animals that reach stage 3–5 (Racine’s scale score) and obtain an AD duration of more than 25 s maintain a similar score and duration at least 1 week after subconvulsive hippocampal stimulation (Tu & Bazan, 2003; Musto et al., 2009). Therefore, in our studies, groups treated with the PAF antagonist, LAU‐0901 (2,4,6‐trimethyl‐1,4‐dihydro‐pyridine‐3,5‐dicarboxylic acid ester), or vehicle (2‐hydroxypropyl‐β‐cyclodextrin,1.4 mg/kg, i.p.…”
Section: Methodssupporting
confidence: 57%
“…In our protocol, direct stimulation of the amygdaloid complex acts as the epileptogenic focus from where epileptic activity spreads toward projection areas that receive amygdala inputs, including hippocampal formation, which exhibited epilepsy-related cellular changes (Lothman et al, 1985; Ikegaya et al, 1996; Aronica et al, 2000; Valentine et al, 2004; Musto et al, 2009). Moreover, the progressive increase in the ADs duration showed that the use of stimulation intensities below the ADs threshold effectively promotes the long-term plasticity described in the kindling model (Racine, 1972a; Abe, 2001; Schubert et al, 2005) minimizing the cellular damage attributable to excessive electrical charge utilized in other protocols (Lothman et al, 1985, 1989; Von Bohlen und Halbach et al, 2004; Fournier et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal stimulation was via a protocol modified from previous studies of fast kindling in mouse models (Smith et al, 2005;Musto et al, 2009;Ledri et al, 2012). Squared current pulses (durations of 0.5 ms) were generated from a Grass stimulator and delivered through an isolation unit (model S88H, Grass Medical Instruments, Warwick RI, USA).…”
Section: Eeg Recordings and Hippocampal Stimulationmentioning
confidence: 99%
“…hippocampus using a protocol adopted from previous studies of fast kindling in mouse models (Smith et al, 2005;Musto et al, 2009;Ledri et al, 2012). A train of high-frequency stimuli (60 Hz for 2 s, at the maximal intensity of 150 A) was applied every 10 min for up to 10 times until stage-5 motor seizures were evoked in individual mice.…”
Section: Sham Controls Post-hi With Ipsilateral Infarctionsmentioning
confidence: 99%